Between Hype and Skepticism: Exploring Generative AI Use in IT Consultancy Work - Forsberg,Filip; Oscarsson,Eric; Sharba,Rim (2025)
This thesis explores the integration of generative AI in IT consultancy, focusing on how consultants and managers perceive its strategic and practical implications in project management. Using a dual-method approach, the study combines semi-structured interviews with AI-driven case experiments to investigate both human perspectives and AI performance. Findings reveal that generative AI is valued for enhancing efficiency, accelerating knowledge access and supporting analytical tasks. However, concerns persist around trust, bias and the need for human oversight. While some organizations are moving toward strategic alignment and structured governance, many remain in experimental stages of adoption. By applying the Strategic Alignment Framework, Data-Driven Decision-Making and Cognitive Bias Theory, the study highlights both the opportunities and limitations of generative AI as a transformative tool. The research concludes that while generative AI holds significant potential, its effective use in consultancy requires critical engagement, strategic intent and responsible governance. This work contributes to a growing body of knowledge on AI in professional services, offering insights into how generative tools can be integrated into consulting workflows and strategic decision-making.
Keywords: Generative AI; Strategy; AI-experiment; IT consultants; AI reliability